2018
DOI: 10.1016/j.oceaneng.2018.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Finite element cable-model for Remotely Operated Vehicles (ROVs) by application of beam theory

Abstract: Increasing autonomy, efficiency and safety for Remotely Operated Vehicles (ROVs) is crucial for future subsea operations and requires accurate models for optimal control, operations and design. This involves precise modeling of the cable in conjunction with the ROV response. This paper presents a novel threedimensional cable model for Remotely Operated Vehicles using Euler-Bernoulli beam theory. The presented model is implemented in Matlab and takes into account the most important effects related to the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Experimental testing methods [19][20][21][22][23] are also applied to research on offshore pipelines. Liang et al [20] conducted experiments to study the dynamic interaction between pipelines and stabbing rollers during pipeline installation.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental testing methods [19][20][21][22][23] are also applied to research on offshore pipelines. Liang et al [20] conducted experiments to study the dynamic interaction between pipelines and stabbing rollers during pipeline installation.…”
Section: Introductionmentioning
confidence: 99%
“…This model is very versatile, and recently is used for some studies found in practical problems as an investigation of the interaction between ship generated waves and slender structures [38] or for the position keeping of a crane barge during use [39]. Furthermore, this model is effectively coupled with the hydro-elastic model of a floating body in regular and irregular waves [40] and with the motions of a remotely operated vehicle (ROV) to assess its efficiency and safety [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a dynamic analysis of the proposed platform was performed through simulation before platform development. The existing studies mainly analyzed the motion between the ROV and the underwater cable while the USV was fixed or analyzed the motion changes of the underwater cable according to the USV motion at high speed [7][8][9][10][11][12][13], but, the unmanned ocean platform proposed in this study performs marine exploration while the USV and UUV move simultaneously. Therefore, it is necessary to analyze the effect of the underwater cable on the movement of the USV and UUV while the platform is moving.…”
Section: Introductionmentioning
confidence: 99%